Measuring Inequality Using J-Bonet Index: What Can We Learn from Regional Data? - Panjawa, Jihad Lukis; Guritno, Danur Condro; Sugiharti, Rr Retno; Kurniawan, Mahrus Lutfi Adi; Damayanti, Sekar Ayu (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
This paper aims to analyze Inequality Using J-Bonet Index Distribution based on regions dimension and its determinant factors. This study uses a quantitative research approach with Quantile Regression (QR) analysis. The results showed that overall, there was no noticeable difference in income inequality among regions. However, according to the status of regions and regions, the expansion area in eastern Indonesia is twice as high as regional income inequality in the parent area in the same region. Other findings, economic growth and poverty cause high-income inequality in eastern Indonesia, while in the western region of Indonesia has no significant effect. In western Indonesia, fiscal decentralization is the cause of high-income inequality between regions, while in eastern Indonesia has no significant effect. Human development has no real impact on income inequality. It is a preliminary study of inequality using J-Bonet and its determinants in Indonesia based on regions dimension with Quantile Regression (QR) as an analysis tool. It can add empirical evidence about the inequality and region dimension.